Development of testing protocols for 13 pyrethroid pesticide products following quantitative and impurities analysis. Supplemented with exposure and toxicity prediction - Lee, Ja Yan (Nanyang Technological University, 2022)
The control of vectors is crucial for public health, resulting in an increase in demand for pesticide products despite its toxicological properties, which highlights the importance of developing testing protocols aiding the regulation of these products. This study primarily aims to develop testing methods for 13 pyrethroid pesticides using 2D-LC-MS/MS (Two Dimensional - Liquid Chromatography with tandem mass spectrometry) in conjunction with the targeted and non-targeted impurity analysis for 9 of the pesticide products using LC-QTOF (Liquid Chromatography – Quadrupole Time-of-Flight) and GC-QTOF (Gas Chromatography - Quadrupole Time-of-Flight). As a secondary goal, RAIDAR-ICE (Risk Assessment Identification And Ranking - Indoor and Consumer Exposure) is adopted for indoor exposure analysis, whilst toxicity prediction is derived by the calculation of Human Equivalent Dose (HED), with the risk prediction of the respective active ingredient compound. Results obtained indicated low detection of active ingredient for 10 pesticide products, with a non-detection of one product. Targeted impurity analysis returned a negative result for all 9 products, with 4 common impurities found through non-targeted impurity analysis. Exposure analysis suggested dermal exposure as the most prominent route indoors, with deltamethrin having the highest predicted toxicity. The risk assessment of respective active ingredient based on exposure and toxicity concluded that the risk is negligible to no adverse effects.